A novel recombinant BCG-expressing pro-apoptotic protein BAX enhances Th1 protective immune responses in mice. Issue 2 (August 2015) - Li, Guanghua; Liu, Guoyuan; Song, Na; Kong, Cong; Huang, Qi; Su, Haibo; Bi, Aixiao; Luo, Liulin; Zhu, Lin; Xu, Ying; Wang, Honghai
Highlights: rBCG::BAX induces macrophage apoptosis in vitro and in vivo. rBCG::BAX facilitates mycobacterial antigen presentation. rBCG::BAX enhances Th1 protective immune responses in mice. Abstract: One-third of the world's population is infected with Mycobacterium tuberculosis (MTB). The protective efficacy of bacille Calmette Guérin (BCG) vaccine against tuberculosis (TB) in adults is highly controversial even though the BCG vaccine has been available for more than 90 years. Because BCG is effective against infantile tuberculosis meningitis and miliary tuberculosis in young children and provides cost-effective prevention from tuberculosis for developing countries, it would be desirable to modify the existing BCG vaccine to provide more comprehensive protection. In our study, we constructed a novel recombinant BCG strain expressing pro-apoptotic BAX (rBCG::BAX) and demonstrated that it significantly induced the apoptosis of macrophages infected with rBCG::BAX both in vitro and in vivo . In addition, it significantly enhanced Ag85B-specific IFN-γ enzyme-linked immunospot responses, IFN-γ secretion, IL-2 secretion and the ratio of Ag85B-specific IgG2b/IgG1, and it significantly decreased Ag85B-specific IL-4. Furthermore, it presumably facilitated antigen presentation by inducing a significant up-regulation in the expression of MHC-II and B7.1 (CD80) co-stimulatory molecules on macrophages. In conclusion, these results suggest that the rBCG::BAX strain elicited predominantly a Th1 protective immune responses and might be a potential tuberculosis vaccine candidate for further study.